HUBUNGAN TINGKAT PENGETAHUAN MASYARAKAT TENTANG CORONAVIRUS DISEASE-2019 (COVID-19) TERHADAP KEPATUHAN PROTOKOL KESEHATAN di RT 08 KERONCONG PERMAI - Alya Ardiana Octariani; Imas Sartika; Lastri Mei Winarni; Hery Saptiadi (Nusantara Hasana Berdikari, 2022)
Covid-19 or Coronavirus Disease-2019 is a serious problem globally, because the number of cases is still increasing. Knowledge about Covid-19 in the community is needed to influence compliance in implementing health protocols. Was to identify the relationship between the level of knowledge about Coronavirus Disease-2019 (Covid-19) and adherence to health protocols. The research design used was a descriptive observational research design. The sampling technique in this study used simple random sampling, with a sample of 146 respondents. Data collection techniques through online based on google form. Analysis of the data used is the frequency distribution for univariate analysis and Spearman's RHO test for bivariate analysis. Showed that the value of Sig (2-tailed) was 0.001, because the value of Sig (2-tailed) was < 0.05, it means that there is a relationship between the level of public knowledge about Covid-19 and compliance with health protocols. A univariate analysis of the level of public knowledge about Covid-19 based on protocol compliance showed the result that the majority of respondents had good knowledge and compliance. Bivariate analysis shows that there is a relationship between the level of public knowledge about Coronavirus Disease-2019 (Covid-19) and compliance with health protocols.